KERAGAAN PERTUMBUHAN BIBIT TANAMAN KAKAO AKIBAT PENGARUH PEMBERIAN BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR DAN DOSIS PUPUK UREA - Irawan Dwiyanto; Moch Arifin; Setyo Budi Santoso; Erwin Prastowo (Plumula : Berkala Ilmiah Agroteknologi, 2021)
Cocoa pod have the potential to be used as an organic fertilizer because of the nutrient content in them. It was reported that 61% of the total nutrients in the cocoa pods are stored in the pod husks themselves. Liquid organic fertilizer derived from cocoa waste by combining EM-4 as a decomposer has an organic C content of 28.24%, a total N of 1, 64%, C / N ratio of 17%, P total 0, 98%, and K total 0.75%. Cocoa pod husk waste has the potential to provide added value to plantation products by further processing it as liquid organic fertilizer (POC) through a fermentation process. For this reason, this study aims to determine the effect of several levels of POC concentration obtained from the processing of cocoa husk waste and its combination with urea fertilizer doses on the growth performance of cocoa seedlings which include plant height, number of leaves, stem diameter and efficiency of N uptake of cocoa plants (ESN). This research was conducted in a greenhouse, Indonesian Coffee and Cocoa Research Center, Jember, and was compiled using a Completely Randomized Design (CRD) consisting of two factors used, namely the level of POC concentration (control, 0.25%, 0.50% and 1%) and the level of urea dose against the recommended dose (control, 10%, 25% and 50%). The analysis showed that the POC combination of cocoa and urea waste was able to increase the average plant height and diameter compared to the control. In addition, the combination of POC 2.5 ml / L and 10% dose of urea resulted in an increase in the efficiency of N uptake in tissues by 44.60%.